Gantzer muscles; a study on 50 cadaveric upper limbs - Bajpe Roshni; R Tarakeshwari; R Shubha (Wolters Kluwer Medknow Publications, 2015)
Background: Gantzer muscle is the name given to the additional head of Flexor Digitorum Profudus (FDP) or Flexor Pollicis Longus (FPL). It connects the superficial flexors and deep flexors of forearm. It sometimes may be related to Anterior Interosseous Nerve (AIN) and Ulnar artery causing Compressive Neuropathy or Vascular symptoms. Aim: To assess incidence of Gantzer muscle in South Indian population, its morphology and clinical significance. Materials and methods: The study was carried out on 50 upper limbs dissected by first year M.B.B.S students. Results: Nine upper limbs showed the presence of Gantzer muscle, three belonged to the right and six belonged to the left. Observations: Additional heads were associated as follows: From FDP-2 and from FPL - 7. Innervation was either from Median nerve, Anterior Interosseous nerve or Ulnar nerve. Superficially median nerve was related, deep relations were Ulnar artery and Anterior Interosseous nerve. In one case, Median nerve and artery were related superficially. Conclusion: Gantzer muscle is important clinically as a cause of vascular or nerve compression.